2018
DOI: 10.1371/journal.pone.0200761
|View full text |Cite
|
Sign up to set email alerts
|

An easy, rapid, and sensitive method for detection of drug-resistant influenza virus by using a sialidase fluorescent imaging probe, BTP3-Neu5Ac

Abstract: Immunochromatographic kits and RT-PCR are widely used as diagnostic tools for influenza detection in clinical and hygiene fields. Immunochromatographic kits are useful for differential typing of influenza A and influenza B but cannot show if the detected virus strains have acquired drug resistance against neuraminidase inhibitors that target sialidase activity of viral neuraminidase. Although RT-PCR enables determination of drug-resistant mutants, its efficacy is limited to viruses carrying a known substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…However, using BTP3-Neu5Ac, it has been shown that the enzymatic activity of sialidase in the hippocampus increases in a short timeframe (in seconds) in conjunction with neuronal excitation. BTP3-Neu5Ac is expanding its range of use, not only for the investigation of physiological functions but also for the detection of colorectal cancer and the influenza virus [ 9 , 74 ]. BTP derivatives can also be used as substrates for hydrolases other than sialidases, such as galactosidase [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using BTP3-Neu5Ac, it has been shown that the enzymatic activity of sialidase in the hippocampus increases in a short timeframe (in seconds) in conjunction with neuronal excitation. BTP3-Neu5Ac is expanding its range of use, not only for the investigation of physiological functions but also for the detection of colorectal cancer and the influenza virus [ 9 , 74 ]. BTP derivatives can also be used as substrates for hydrolases other than sialidases, such as galactosidase [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using a combination of a virus-concentrated membrane in a centrifugal filter unit and BTP3-Neu5Ac, the sialidase activity of influenza neuraminidase can be easily detected on the membrane by green fluorescence under UV irradiation with a handheld UV flashlight [ 74 ]. The assay can be completed within 15 min.…”
Section: Detection Of Influenza Virusesmentioning
confidence: 99%
“…Tamiflu, also known as oseltamivir phosphate 1 is a potent chemotherapeutic agent for influenza treatment [ [1] , [2] , [3] ] Influenza is a severe viral infection of the respiratory system regarded as the most serious respiratory disease, which is responsible for significant morbidity and mortality due to both annual epidemics and predictable pandemics [ [1] , [2] , [3] ] More specifically, the avian influenza H5N1 has a mortality rate of about 60% [ 4 ] Unfortunately, little has been done to change the influenza infection patterns in past decades despite influenza being the most studied viral infection before the arrival of the human immunodeficiency virus (HIV) [ 5 , 6 ] Now in this global society, a highly aggressive strains of the influenza virus such as the H5N1 can mutate to become easily transmitted from human to human and spark another deadly pandemic just as with current Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection (COVID19) pandemic, [ 7 , 8 ] which has brought the world to its knees. The surge in drug-resistant influenza strains resulting from naturally occurring mutations reminds us of the need for continued research to discover more potent neuraminidase inhibitors [ [9] , [10] , [11] , [12] , [13] ] The current anti-influenza drugs are useful templates in the development of new neuraminidase inhibitors through structure-activity relationship studies. As the research towards new and better treatment remains a top priority, it is equally important to improve the availability of the current anti-influenza drugs by developing better synthetic procedures to guard the world against influenza.…”
Section: Introductionmentioning
confidence: 99%
“…37−49 In recent years, several optical probes have been developed based on NA for influenza virus detection or imaging. A series of BTP-Neu5Ac analogues, developed by the Suzuki group, are fluorogenic and precipitating probes, which have been used to image colon cancer tissue sialidases, 50 influenza virus neuraminidase, 33,51,52 and sialidase activity in rat brain. 52 The CLNA, NA-Star, and ZstatFlu, as 1,2dioxetane based chemiluminescence probes, have been developed as chemiluminescent neuraminidase probes for IAV rapid detection in mammalian cells.…”
mentioning
confidence: 99%